Application of Bipolar Fuzzy Set to a Novel of Fuzzy Ideal in $Γ$-Semigroups (European Journal of Pure and Applied Mathematics, 2023)
In this paper we define new types of bipolar fuzzy ideals, bipolar fuzzy almost ideals in $Γ$-semigroups. We discussed properties of bipolar fuzzy ideals, bipolar fuzzy almost ideals, minimal bipolar fuzzy ideal, minimal bipolar almost ideal in $Γ$-semigroups. Moreover, we prove connection between almost ideals and bipolar fuzzy almost ideals of $Γ$-semigroups.
Keywords: bipolar fuzzy ideals; bipolar fuzzy almost ideals; minimal bipolar fuzzy ideals; minimal biploar fuzzy almost ideals